Concurrent Use of Alcohol and Sedatives Among Persons Prescribed Chronic Opioid Therapy: Prevalence and Risk Factors - Saunders, Kathleen W; Von Korff, Michael; Campbell, Cynthia I; Banta-Green, Caleb J; Sullivan, Mark D; Merrill, Joseph O; Weisner, Constance (The journal of pain, 2012)
Abstract Taking opioids with other central nervous system (CNS) depressants can increase risk of oversedation and respiratory depression. We used telephone survey and electronic health care data to assess the prevalence of, and risk factors for, concurrent use of alcohol and/or sedatives among 1,848 integrated care plan members who were prescribed chronic opioid therapy (COT) for chronic noncancer pain. Concurrent sedative use was defined by receiving sedatives for 45+ days of the 90 days preceding the interview; concurrent alcohol use was defined by consuming 2+ drinks within 2 hours of taking an opioid in the prior 2 weeks. Some analyses were stratified by substance use disorder (SUD) history (alcohol or drug). Among subjects with no SUD history, 29% concurrently used sedatives versus 39% of those with an SUD history. Rates of concurrent alcohol use were similar (12 to 13%) in the 2 substance use disorder strata. Predictors of concurrent sedative use included SUD history, female gender, depression, and taking opioids at higher doses and for more than 1 pain condition. Male gender was the only predictor of concurrent alcohol use. Concurrent use of CNS depressants was common among this sample of COT users regardless of substance use disorder status. Perspective Risks associated with concurrent use of CNS depressants are not restricted to COT users who abuse those substances. And, the increased risk of concurrently using CNS depressants is not restricted to opioid users with a prior SUD history. COT requires close monitoring, regardless of substance use disorder history.